(untitled) (Innovate Conferences, 2025)
Bone grafting is an essential surgical technique in reconstructive and regenerative medicine aimed at restoring bone defects resulting from trauma, pathology, or congenital anomalies. The selection of a specific bone grafting method depends on the defect’s size, location, biological properties of the graft material, and the patient’s overall health. This study analyzes the clinical rationale for the use of autografts, allografts, xenografts, and synthetic bone substitutes, comparing their biological integration, mechanical stability, and potential complications.